2014
DOI: 10.1007/s11118-014-9444-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude, Diversity, Capacities, and Dimensions of Metric Spaces

Abstract: Magnitude is a numerical invariant of metric spaces introduced by Leinster, motivated by considerations from category theory. This paper extends the original definition for finite spaces to compact spaces, in an equivalent but more natural and direct manner than in previous works by Leinster, Willerton, and the author. The new definition uncovers a previously unknown relationship between magnitude and capacities of sets. Exploiting this relationship, it is shown that for a compact subset of Euclidean space, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(80 citation statements)
references
References 16 publications
1
79
0
Order By: Relevance
“…The lower bound was proved in [19,Theorem 3.5.6] for p = 1 and [27,Theorem 4.5] for the general case. 1 The proof here follows the approach used in [28] for ℓ n 2 (see Proposition 5.6 and the remarks following Corollary 5.3 there).…”
Section: 3mentioning
confidence: 94%
See 4 more Smart Citations
“…The lower bound was proved in [19,Theorem 3.5.6] for p = 1 and [27,Theorem 4.5] for the general case. 1 The proof here follows the approach used in [28] for ℓ n 2 (see Proposition 5.6 and the remarks following Corollary 5.3 there).…”
Section: 3mentioning
confidence: 94%
“…Let k = R, and define |·| : [0, ∞] → R to be either the indicator function of [0, 1] or that of [0, 1). It is shown in Section 8 of [28] that these are essentially the only possibilities for |·|, and that the resulting magnitude of a finite ultrametric space is simply the number of balls of radius 1 (closed or open, respectively) needed to cover it. It is also shown that this leads naturally to the notion of ε-entropy or ε-capacity.…”
Section: Examples 23mentioning
confidence: 99%
See 3 more Smart Citations